THE EFFECT OF DISPOSITION ON STUDENT MATHEMATICS LEARNING ACHIEVEMENT IN MEDAN STATE 28 JUNIOR HIGH SCHOOL - Siregar, Machrani Adi Putri; Lisma, Eryanti (Universitas Negeri Medan, 2019)
This study titled as The Effect of Disposition on Student Mathematics Learning Achievement in Medan State 28 Junior High School. In this study, disposition is an independent variable and achievement in mathematics learning is a dependent variable. Mathematical disposition is a change of student’s tendency in assuming and behaving toward mathematics, also their act when learning mathematics. For example, when students can solve non-routine problems, their behavior and assumption of mathematics as a student become more positive. The more mathematical concepts understood, the more students convinced that mathematics can be mastered. Based on theory, there are many factors that influence student's achievement in mathematics learning. In this study, researcher only took disposition factor. This research took place at Medan State 28 Junior High School which located at Karya Bersama St. No. 17 Medan Johor. The method of this study is a quantitative method with all of VIII class students which amount to 273 students and divided into 8 (eight) study groups. The data obtained by giving a questionnaire consisting of 19 statements. The data then analyzed by using simple linear regression analysis. The data analysis was performed by using SPSS 21 software for Windows. From the results of this study, it can be concluded that there is an effect of disposition on students' achievement in mathematics learning or in other words, students' achievements in mathematics learning are influenced by the disposition attitudes that students have in mathematics learning. The influence occurs in the disposition of achievement in mathematics learning is positive, that is equal to 6.6%.Keywords: Disposition, Mathematics Learning Achievement.